원통형 캐비티에서 방출되는 방사 전자파 특성 - 김효균(Hyo-Gyun Kim); 조준호(Jun-Ho Cho); 임동영(Dong-Young Lim); 김기채(Ki-Chai Kim) (한국정보통신학회논문지, 2016)
This paper, presents the characteristics of electromagnetic fields radiated from a pole-transformer. The cylindrical cavity is used to measure electromagnetic fields radiated from a pole-transformer when partial discharge occures inside the pole-transformer. The theoretical analysis is conducted by a finite difference time domain (FDTD) method. As a result, frequency characteristics of the radiated electromagnetic waves emitted from the inside the cavity to the outside through the 1st and 2nd bushings could be observed for the configuration of the cylindrical cavity with a radiation window. The frequency characteristics of electromagnetic field are also studied according to the enclosure structure of the cylindrical cavity. To verify the theoretical analysis, computed results are compared to experimental results. 본 논문에서는 주상변압기의 내부 부분방전에 의한 방사 전자파를 예측하기 위해 원통형 캐비티의 구조 및 크기 변화에 따른 1차측, 2차측 전극의 부싱을 통해 방출되는 방사 전자파 특성을 FDTD 법으로 검토하였다. 그 결과, 원통형 캐비티의 구조에서 1차측 및 2차측 부싱에서 방사되는 방사 전자파를 확인할 수 있었다. 원통형 캐비티 외함의 구조에 대한 방사 전자파의 주파수 특성을 검토하고 제작한 원통형 캐비티의 실험을 통해 이론 계산 결과와 비교 검토하였다.